Current Trends in ELT - Kim, Yong (JET (Journal of English Teaching), 2011)
Owing to the use of English as a global lingua franca, the trends in English teaching could probably be well perceived by considering the language’s inseparability from globalization. First of all, since globalization has affected almost the whole aspects of life in the world, English, which is used as the main means of communication in those sectors, is also closely connected to them. Consequently, any consideration of the teaching of English should be linked to them. Secondly, its multiple forms or uses in some specific locations has emerged the phenomena of Englishes and been challenged as the only type to be learned. Finally, the massive use of ICT has also contributed to the many new possibilities of using technology for teaching English.